Spinning straw into gold: Innovation recycling, innovation sourcing modes, and innovation ability in Sub‐Saharan Africa. Issue 5 (1st August 2022) - Li, Rebecca Yu; Sousa, Carlos M. P.; He, Xinming; Hu, Yansong
Abstract: As innovation is inherently risky and uncertain, it is common for firms to suspend or abandon new product/service development projects that cannot achieve pre‐defined objectives. Multiple cases exist where firms have attempted to resume the development of an innovative product or service after previously suspending or abandoning it prior to completion. Research on this important innovation recycling activity is surprisingly scarce, despite its critical role in mitigating risk in the context of high environmental uncertainty. We draw our inferences from Sub‐Saharan Africa (SSA), where innovation resources are relatively limited and environmental uncertainty and institutional voids prevail, a context that encourages the use of innovation recycling. This study examines how innovation recycling influences a firm's innovation ability and the moderating impact of innovation sourcing modes using a knowledge‐based view of the firm and arguments from transaction cost economics. We retrieved data from the World Bank Enterprise Survey and the Innovation Follow‐up Survey of 1076 firms located in eight SSA countries (Ghana, Malawi, Namibia, South Sudan, Sudan, Tanzania, Uganda, and Zambia) spanning from 2011 to 2014 to test our conceptual model. Our findings show that (1) innovation recycling has a positive influence on a firm's innovation ability and (2) this relationship is moderated by different innovation sourcing modes. These findings enrich the theory and imply that firms operating in developing countries need to develop innovation recycling by focusing on sourcing knowledge within, rather than across, firm boundaries.